2012
DOI: 10.1111/hae.12044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the thrombin generation assay in haemophilia: Comparative study between fresh and frozen platelet‐rich plasma

Abstract: The severity of haemophilia A has traditionally been classified by the dosage of factor VIII (FVIII) by one-step coagulation tests. However, an homogeneous group of patients with similar FVIII levels show clinical heterogeneity and 10-15% of the patients classified as severe haemophilia do not have a severe bleeding phenotype. Traditional tests used for measuring FVIII are not capable of detecting other prohaemorrhagic or prothrombotic factors. Global tests as the thrombin generation assay (TGA) may detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Previous data have shown marked increases in thrombin generation capacity in PRP specimens compared to PPP [20]. An interesting hypothesis is that TEG is performed in the whole blood milieu; therefore, it is possible some FVIII remains in or on the platelet despite unmeasurable FVIII activity.…”
Section: Discussionmentioning
confidence: 98%
“…Previous data have shown marked increases in thrombin generation capacity in PRP specimens compared to PPP [20]. An interesting hypothesis is that TEG is performed in the whole blood milieu; therefore, it is possible some FVIII remains in or on the platelet despite unmeasurable FVIII activity.…”
Section: Discussionmentioning
confidence: 98%
“…The desired outcome of 95% of observations deviating less than AE10% was not obtained for any of the groups or parameters tested [11]. In a similar study by Vila et al [9], no significant differences between f-PRP and ft-PRP were found, but the level of agreement was not determined. As systematic differences between observations will result in a high degree of correlation and the absence of significant difference between groups may be attributable to a small number of observations, it cannot be ruled out that the level of agreement was also low in the Vila study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of frozen-thawed PRP (ft-PRP) has been questioned in several articles [7,8]. However, in a study in which fresh PRP (f-PRP) was compared to ft-PRP there were no significant differences between the parameters, opening up opportunities for the use of ft-PRP in multicentre studies [9]. The aim of our study was to investigate the level of agreement between f-PRP and ft-PRP to further validate these results.…”
Section: Introductionmentioning
confidence: 99%
“…The TEG and TGA profiles observed in this study could be explained by the same mechanism of action because both assays are TF-driven assays, but studies on patients with other coagulation factor (CF) deficiencies (e.g. severe haemophilia A or haemophilia A with inhibitors) showed similar results, suggesting that TEG and TGA can be used to measure the CF defect in general but do not reflect a specific CF defect or its underlying mechanism [26,27]. One exception is MCF, a TEG parameter that measures clot stability and is more sensitive for deficiency in FXIII and fibrinogen than for other CF deficiencies.…”
Section: Discussionmentioning
confidence: 57%